Israel : 2022 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2022)
The Israeli economy has weathered the COVID-19 crisis exceptionally well, but risks are high. With substantial fiscal and monetary support, real GDP growth reached 8.1 percent in 2021, driven by consumption and high-tech exports. The rapid vaccination campaign boosted confidence. The outlook is positive but still subject to high uncertainty.